Argentina: Strong linkage between IHRL and domestic law - Clérico, Laura; Novelli, Celeste (Edward Elgar Publishing Ltd., 2021)
This chapter examines the implementation and compliance with International Human Rights Law in Argentina. To attain that objective, this work takes into consideration the leading role of Argentina related initially to the investigation and prosecution of gross human rights violations committed during the last military dictatorship, and which has certainly contributed to the development and strengthening of the Inter-American System in the region. This is the point of departure for analyzing the strong linkage between international human rights law and national law that was reinforced by the constitutionalisation of the main human rights declarations and treaties since. We sustain that this linkage could not have happened without case law giving meaning to this linkage. Besides human rights movements, organizations, and defenders in accordance with the decisions of international human rights bodies have contributed to the strengthening and the effectiveness of human rights norms and their compliance, as well as some coalitions among Legislative, Executive and Judicial Power, which have converted the respect of human rights law into a matter of state policy. Additionally, the work explores the procedures, institutions and practices developed by federal and provincial structures in order to guarantee the implementation of supranational rulings, especially the decisions taken by the Inter-American Court and the Inter-American Commission of Human Rights. Finally, this works outlines the significant role of human rights organizations and victims in litigating and monitoring compliance concerning the protection of human rights in Argentina.
CRIS-Team Scopus Importer:2023-03-21